32. Quantitative EEG evaluation during robot-assisted foot movement. Issue 12 (December 2016) - Del Felice, A.; Masiero, S.; Bosco, A.; Izzi, F.; Piccione, F.; Formaggio, E.
Abstract : Passive and imagined limb movements induce changes in cerebral oscillatory activity. Central modulatory effects play a role in plastic changes, and are of uttermost importance in rehabilitation. This has extensively been studied for upper limb (UL), but less is known for lower limb (LL). The aim of this study is to investigate the topographical distribution of event-related desynchronization/synchronization (ERD/ERS) and task-related coherence during a robot-assisted and a motor imagery task of lower limb in healthy subjects. 32-channels electroencephalogram (EEG) was recorded in twenty-one healthy right handed subjects during a robot-assisted single-joint cyclic right ankle movement performed by the BTS ANYMOV robotic hospital bed. Data were acquired with a block protocol for passive and imagined movement at a frequency of 0.2 Hz. ERD/ERS and task related coherence were calculated in alpha1 (8–12 Hz), alpha2 (10.5–12.5 Hz) and beta (13–30 Hz) frequency ranges. During passive movement, alpha2 rhythm desynchronized over the contralateral sensori-motor area and ipsilateral prefrontal cortex, and beta over the bilateral SM. During motor imagery, a significant desynchronization was evident for alpha1 over contralateral SM, for alpha2 over bilateral SM, and for beta over central scalp areas. No statistically significant difference emerged from the two conditions. Task-related coherence decreased in alpha2 band between left central - right frontal and left central – left parietal areas; beta band coherence decreased between C3–C4 electrodes, and increased between C3–Cz. These data contribute to the understanding of oscillatory activity during lower limb robot-assisted motor performance, and point to the advantages of this analysis to evaluate cortical oscillations changes.